Determination of nitrate, phosphate and potassium with different inoculums composition in restaurant waste - Liew, Jee Nin, 1987-; Hashim Baharin, supervisor; Fakulti Sains (2009)
Project Paper (Sarjana Muda Sains (Kimia Industri)) - Universiti Teknologi Malaysia, 2009